CAN TRANSITIONAL CARE DECREASE READMISSION IN STROKE PATIENTS? - Yurike Septianingrum; Siti Nurjanah; Nursalam Nursalam (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: One strategy to reduce the hospital readmission rate of stroke patients is to implement transitional care. Objective: The aim of this study was to identify the application of transitional care to the hospital readmission rate of stroke patients. Design: Design of this literature review was A Systematic review. Data Sources: We searched English articles in PubMed, CINAHL, SAGE, and Science Direct databases from January 2016 to September 28, 2021. Participants in the study were adults (17 years old or older) who had transitioned from hospital to home care. The included publications were mined for information on study features and research findings. Review Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement was followed when conducting this review. The study question and search method were developed with the aid of the PICO framework, which provides descriptions of participants, interventions, comparisons, and results. Results: Eight articles were reviewed regarding the outcomes of implementing transitional care on readmission rates and satisfaction in stroke patients. All reviewed articles showed decreased readmission rates and increased patient satisfaction. There were some differences in the transitional care process, team coordinator, duration of transition care follow-up, and service satisfaction. Conclusion: Our findings show that the application of transitional care has a positive impact on decreasing readmission rates before 30 days and increasing patient satisfaction with nursing care. Transitional care policies need to be considered to reduce readmission rates in an effort to improve the quality of hospital services.